Mountain streams flushing litter to the sea – Andean rivers as conduits for plastic pollution. (15th December 2021) - Honorato-Zimmer, Daniela; Kiessling, Tim; Gatta-Rosemary, Magdalena; Kroeger Campodónico, Celeste; Núñez-Farías, Paloma; Rech, Sabine; Thiel, Martin
Abstract: Rivers polluted by anthropogenic litter are major transport routes of litter from inland to the coastal zone and the ocean. However, litter studies have primarily focused on marine environments, and the litter dynamics in rivers are still poorly understood. Herein, we explored the abundances, composition and sources of litter at the riversides and in surface waters of mountain rivers from continental Chile in two different years. Additionally, we evaluated whether different temporal, geographic, topographic, hydrologic or anthropogenic factors influence the abundances of litter. Anthropogenic litter was prevalent in Chilean rivers, both at the riversides and in surface waters. Average abundances of riverside litter, floating macrolitter, and small floating plastics were 1.8 items m −2, 10.1 items h −1 and 5.8 items h −1, respectively, and abundances were generally higher in northern Chile. Plastics dominated in all compartments, comprising 29% of riverside litter and more than 70% of small floating litter, but other litter categories were also present at riversides. Sources of litter in Chilean rivers were mostly local, such as recreational visitors, residents, and illegal dumping, and there were no clear effects of the different tested factors on the abundances of litter. Litter densities in surface waters were low compared to those in lowland slow-flowing rivers in other countries, suggesting that retention of litter is limited in the highly dynamic and rapidly flushing mountain rivers, and thus most litter (primarily plastics) is transported directly to the sea. The results suggest that to adequately address this problem in Chile, prevention measures should be aimed at the identified local sources, by means of education, public policies, legislation, and enforcement.